2017
DOI: 10.3892/mco.2017.1202
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous primary malignant neoplasms of the cervix and endometrium

Abstract: Synchronous multiple malignant neoplasms of the female genital tract are rare, particularly in the uterus. We herein present the case of a patient with synchronous cervical squamous epithelial carcinoma and endometrial adenocarcinoma, and discuss the diagnosis, treatment and prognosis. The patient underwent a cervical biopsy and fractional curettage of the endometrium, followed by abdominal staging surgery, including radical hysterectomy, bilateral salpingo-oophorectomy, pelvic and para-aortic lymphadenectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To date, only 6 cases of concomitant endometrial and cervical cancer have been reported. [ 5 , 6 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only 6 cases of concomitant endometrial and cervical cancer have been reported. [ 5 , 6 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Radical hysterectomy has been recommended for those with stage IB1 cervical cancer. [ 11 ] Patients with high-level risk factors require extensive adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested follow-up with chest x ray and Pap smear from vaginal stump for ruling out of metastatic endometrial cancer to lungs and recurrence of cervical carcinoma respectively. They proposed a prognosis better than metastasis and worse than metachronous tumors by considering clinical stage [12]. Ayhan A and the colleagues evaluated 29 patients with synchronous genital malignancies.…”
Section: Discussionmentioning
confidence: 99%